Renal Anastomosing Hemangiomas With a Diverse Morphologic Spectrum: Report of Two Cases and Review of Literature. (June 2014) - Chou, Shaun; Subramanian, Vishnu; Lau, Howard M. H.; Achan, Anita
Benign vascular lesions have a diverse appearance and can be extremely difficult to classify. We present renal anastomosing hemangiomas from 2 patients that exemplify the potential diverse range of appearances that can occur in this recently described, rare variant of capillary hemangioma. The lesion from one patient was an intravenous hemangioma with closely packed, fenestrated vascular channels that were reminiscent of the splenic red pulp. Also, the endothelial cells contained hyaline globules. On the other hand, the second patient had multifocal tumor. The lesions showed more extensive hyalinization and vascular ectasia reminiscent of cavernous hemangioma. Extramedullary hematopoiesis was a feature in all the tumors, particularly in the second patient where numerous immature blasts were present within vascular spaces.